2022
DOI: 10.51248/.v42i1.662
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of self-directed learning and traditional teaching method in understanding cardio- respiratory physiology among medical undergraduates

Abstract: Introduction and Aim: Active and learner centred learning methods specially, self-directed learning is considered to be an important method of blended learning approach of imparting knowledge among under graduate medical students in new curriculum through integrated approach. The aim of the study is to analyse the impact and benefits of self-directed learning sessions for understanding cardio- respiratory physiology among phase one MBBS students. Design and Methods: This cross-sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The topics learned through the self-learning method were better retained in memory, and students performed better in the follow-up test on that topic conducted 15 days later. Studies conducted in the past have asserted that the self-directed learning method is a more effective way of delivering concepts as compared to traditional lecture sessions [16][17][18]. Despite better performance, only 40.8% of the students opted for the self-learning method as the preferred mode.…”
Section: Discussionmentioning
confidence: 99%
“…The topics learned through the self-learning method were better retained in memory, and students performed better in the follow-up test on that topic conducted 15 days later. Studies conducted in the past have asserted that the self-directed learning method is a more effective way of delivering concepts as compared to traditional lecture sessions [16][17][18]. Despite better performance, only 40.8% of the students opted for the self-learning method as the preferred mode.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis, which included over 100 medical and dental students in both treatment and control groups, showed a significant overall effect of stress reduction as a result of the yoga intervention, as measured by standardized assessments [ 43 , 46 , 47 , 51 , 54 , 57 ]. Similarly, studies focusing on the effect of yoga on anxiety, with sample sizes of 114 and 160 participants in the intervention and control groups respectively, demonstrated a significant reduction in anxiety as measured by standardized tests [ 30 , 43 , 44 , 48 , 55 , 57 ]. In addition to the positive impacts on stress and anxiety, our systematic-review found a notable decrease in depression among those participating in the yoga group [ 45 , 49 , 53 , 55 , 56 ].…”
Section: Impact Of Yoga On Psychological Well Beingmentioning
confidence: 99%